Chemistry, structures, and advanced applications of nanocomposites from biorenewable resources - Ates, Burhan; Koytepe, Suleyman; Ulu, Ahmet; Gurses, Canbolat; Thakur, Vijay Kumar (American Chemical Society, 2020)
Researchers have recently focused on the advancement of new materials from biorenewable and sustainable sources because of great concerns about the environment, waste accumulation and destruction, and the inevitable depletion of fossil resources. Biorenewable materials have been extensively used as a matrix or reinforcement in many applications. In the development of innovative methods and materials, composites offer important advantages because of their excellent properties such as ease of fabrication, higher mechanical properties, high thermal stability, and many more. Especially, nanocomposites (obtained by using biorenewable sources) have significant advantages when compared to conventional composites. Nanocomposites have been utilized in many applications including food, biomedical, electroanalysis, energy storage, wastewater treatment, automotive, etc. This comprehensive review provides chemistry, structures, advanced applications, and recent developments about nanocomposites obtained from biorenewable sources.
Keywords: Bio-renewable sources; nanocomposites; natural polymers; reinforcement; advanced applications